Sex Differences in Music: A Female Advantage at Recognizing Familiar Melodies - Miles, Scott A.; Miranda, Robbin A.; Ullman, Michael T. (Frontiers in Psychology, 2016)
Although sex differences have been observed in various cognitive domains, there has been little work examining sex differences in the cognition of music. We tested the prediction that women would be better than men at recognizing familiar melodies, since memories of specific melodies are likely to be learned (at least in part) by declarative memory, which shows female advantages. Participants were 24 men and 24 women, with half musicians and half non-musicians in each group. The two groups were matched on age, education, and various measures of musical training. Participants were presented with well-known and novel melodies, and were asked to indicate their recognition of familiar melodies as rapidly as possible. The women were significantly faster than the men in responding, with a large effect size. The female advantage held across musicians and non-musicians, and across melodies with and without commonly associated lyrics, as evidenced by an absence of interactions between sex and these factors. Additionally, the results did not seem to be explained by sex differences in response biases, or in basic auditory or motor processes as tested in a control task. Though caution is warranted given that this is the first study to examine sex differences in familiar melody recognition, the results are consistent with the hypothesis motivating our prediction, namely that declarative memory underlies knowledge about music (particularly about familiar melodies), and that the female advantage at declarative memory may thus lead to female advantages in music cognition (particularly at familiar melody recognition). Additionally, the findings argue against the view that female advantages at tasks involving verbal (or verbalizable) material are due solely to a sex difference specific to the verbal domain. Further, the results may help explain previously-reported cognitive commonalities between music and language: since declarative memory also underlies language, such commonalities may be partly due to a common dependence on this memory system. More generally, because declarative memory is well studied at many levels, evidence that music cognition depends on this system may lead to a powerful research program generating a wide range of novel predictions for the neurocognition of music, potentially advancing the field.